Dysphemism in the Novel A Portion of Chicken Noodles Before Dying: Analysis of Meaning, Form, Function, and Classification - Linda Yulia Putri; Rahimatul Uthia; Nur Azizah; Widhi Choirunisa Putri; Yulinda Sahara; Farel Olva Zuve (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The novel Seporsi Mie Ayam Sebelum Mati represents the realities of the characters’ lives through the use of a firm, direct, and harshly nuanced style of language. One of the prominent linguistic features in this novel is dysphemism, which is employed as a stylistic device to openly depict conflict, emotional outbursts, and social criticism. In linguistic studies, dysphemism is not merely understood as the use of coarse expressions, but rather as a linguistic strategy that serves aesthetic and pragmatic functions in constructing literary meaning. Therefore, an analysis of dysphemism in this novel is essential to reveal the deepening of characterization and the social messages conveyed by the author. This study aims to describe the forms, classifications, and functions of dysphemism in the novel Seporsi Mie Ayam Sebelum Mati. The research was conducted through a library-based study, with the novel serving as the primary data source. The research population comprises all linguistic units found in the novel, while the research sample consists of words, phrases, and expressions containing dysphemistic elements. The research instruments include data cards and a dysphemism classification guideline based on stylistic and pragmatic theories. Data analysis was carried out qualitatively using content analysis techniques through the stages of identification, categorization, interpretation, and conclusion drawing. The results indicate that dysphemism in the novel can be classified into four forms: insults, mockery, negative labeling, and pejoration. These dysphemistic expressions function to realistically represent the characters’ emotions, construct characterization, strengthen plot dynamics, and convey social criticism both implicitly and explicitly.